The Application of Shari'ah Principles of Adr in Malaysia Construction Industry. - Zuhairah Ariff, A.G.; Abdul Majid Tahir, M.; Farhanin, A.A.; Rozina, M.Z. (2016)
In Malaysia the implementation of alternative dispute resolution (ADR) in the construction industry mainly concentrates on arbitration. Being one of the standard contractual terms in building contracts, arbitration is one of the measures adopted to resolve disputes between contractual parties. Other methods of ADR includes mediation and adjudication. With the introduction of Construction Industry Payment and Adjudication Act 2012 (CIPAA), adjudication is also emerging as a method to resolve disputes on payment issues in construction contracts. Under the Islamic law, an amicable settlement of disputes, either in personal or commercial matters is encouraged and allowed, except if it shall turn something from prohibited (haram) into permitted (halal) or from permitted (halal) into prohibited.